2019
DOI: 10.4034/pboci.2019.191.109
|View full text |Cite
|
Sign up to set email alerts
|

Ideal Concentration of Advanced-Platelet Rich Fibrin (A-PRF) Conditioned Media for Human Dental Pulp Stem Cells Differentiation

Abstract: Objective: To discover the ideal concentration of Advanced Platelet Rich Fibrin (A-PRF) as modification of PRF, for human Dental Pulp Stem Cells (hDPSCs) differentiation. Material and Methods: hDPSCs were devided into five experimental groups: Group I (control group) consist of hDPSCs cultured in 10% FBS, Group II consist of hDPSCs cultured in 1% A-PRF, Group III consist of hDPSCs cultured in 5% A-PRF, Group IV consist of hDPSCs cultured in 10% A-PRF and Group V consist of hDPSCs cultured in 25% A-APRF. All gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…In this study, the highest expression of TGF-β1 was found in 25% A-PRF culture media supplement, whereas the lowest was observed at 1% concentration. This is consistent with the results of Bagio et al (2019) who reported that the highest expression of DSPP in the odontogenic differentiation of hDPSCs was obtained at 1% A-PRF and the lowest at a concentration of 25%. The presence of TGF-β1 in the culture media can stimulate the differentiation process, but if the amount is too high, it can be toxic and inhibit the process of differentiation itself [5,13,16,17].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, the highest expression of TGF-β1 was found in 25% A-PRF culture media supplement, whereas the lowest was observed at 1% concentration. This is consistent with the results of Bagio et al (2019) who reported that the highest expression of DSPP in the odontogenic differentiation of hDPSCs was obtained at 1% A-PRF and the lowest at a concentration of 25%. The presence of TGF-β1 in the culture media can stimulate the differentiation process, but if the amount is too high, it can be toxic and inhibit the process of differentiation itself [5,13,16,17].…”
Section: Resultssupporting
confidence: 93%
“…This step is accompanied by a slight increase in centrifugation time, resulting in the so-called advanced PRF (A-PRF) [4]. A-PRF produces the maximum GF levels compared with PRP [5].…”
Section: Introductionmentioning
confidence: 99%
“…Saaed et al also demonstrated that 10% PRF exudate (PRF-Ex) can replace FBS as CM for hDPSCs and increase their differentiation ability into osteogenic cells [23]. The potential of A-PRF as a culture medium for hDPSCs has also been reported by Bagio et al [24], who showed that 1%-5% A-PRF CM induces the dentin sialophosphoprotein (DSPP) expression of hDPSCs; furthermore, Alizarin red results showed the osteogenic differentiation of hDPSCs after 7 days of culture [24]. These results correlate with the osseointegration relationship in the ability of human MSCs (hMSCs) to express VEGF that exerts signaling with osteoblast differentiation [25].…”
Section: Introductionmentioning
confidence: 74%
“…Bagio et al proved that the ideal concentration of A-PRF, which have great potential ability of human DPCs' odontogenic differentiation, is at 1 to 5%. 24 From this result, various concentrations of A-PRF as well as L-PRF, as allogenic platelet concentrations, which are platelet-rich blood derivatives, have been widely used in stem-cell-based therapy as CM showed a great potential of stem cells' migration.…”
Section: Discussionmentioning
confidence: 99%